Evaluating the e-GP system in Bangladesh Water Development Board (BWDB) - Md. Ruhunnabi, Abdullahil Baki (BRAC University, 2016)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.